The influence of human resource management practices on employee engagement at Port Klang authority - Thilagavili, Mariappan (2017)
The aim of the study is to determine the Human Resource Management (HRM) practices, namely supervisory behavior, employee communication and employee development, that influenced employee engagement of the employees at Port Klang Authority (PKA). This quantitative study was conducted among 152 PKA employees. The data were analyzed by using The Statistical Package for Social Sciences (SPSS) version 19. The findings showed that employee development was the only independent variable had a positive and significant impact on employee engagement. Recommendations and implications for future study and practices were also revealed.